A research on the culture values of Singapore and the impact on work related behaviours. - Hong, Luanne Yu Hui. (2008)
The main purpose of this study is to investigate how culture values affect the work attitudes and behaviours of Singaporean managers and professionals. Comparisons were made between business students and professionals/managers in Singapore.